European Glaucoma Society Terminology and Guidelines for Glaucoma, 5th Edition (British journal of ophthalmology, 2021)
ForewordThe only time is now. Every “now” is unique. Responsible persons ask themselves, “How can I act well now?” The answers will differ for every person, because just as every situation is unique, so is every person different from every other person. But surely there must be some algorithm that will assist us in coming to the right answer. Unfortunately, no, for there is no right answer. There is only an answer that is as appropriate as we can conclude at that moment in that situation. No written guidelines can apply appropriately to every unique situation.Unfortunately we physicians have been suckled on a fallacy: “What’s good for the goose is good for the gander.” Phrased in medical terms, “normal findings are good, and abnormal findings are bad.” This is too simple, and often wrong.Good clinicians know that care must be personalized for it to be optimal. So-called normal findings give rough guidance, sometimes applicable to groups, but frequently wrong for individuals. Consider intraocular pressure (IOP). A normal IOP of 15 mmHg good for some and bad for others, and an abnormal IOP of 30 mmHg is good for some and bad for others. We are so bombarded by the myth of the sanctity of the standard distribution curve that it is hard to think independently and specifically. Also, unfortunately, doctors are prone to decide for patients, often on the basis of normative data that is not relevant or important for the particular patient. That we do this is not surprising, as we want to help, and so we default to what seems to be the easy, safe (non-thinking) way, in which we do not have to hold ourselves accountable for the outcome.Somebody HAS to decide, or else we would be living in an anarchical world. Also true. And because none of us knows as much as we need to know to act appropriately, we seek advice from so-called “experts.”For us to care for people well it is essential that we consider what others recommend. So we look to experts, as we should. However, experts are sometimes right and sometimes wrong. Remember that von Graefe in 1860 recommended surgical iridectomy for all glaucoma, Elliot recommended mustard plaster between the shoulders for glaucoma, Becker based treatment on tonographic findings, Weve reported 100% success with penetrating cyclodiathermy in glaucoma, Lichter advised against laser trabeculoplasty, many thought Cypass was great, and the investigators in the Advanced Glaucoma Intervention Study indicated that an IOP usually around 12 mmHg was better than one usually around 20 mmHg. All wrong. What the authors of these guidelines have done excellently, is to provide a general framework on which ophthalmologists can hang pieces of evidence, so as to be able to evaluate the validity and the importance of that evidence. In doing this meticulously they have provided a valuable service to all ophthalmologists, none of whom individually have either the time or the skill to be fully informed. In their own practices the authors consider whether valid information is relevant for the particular person being considered. That process of considering relevance is essential, always. And relevance is based on the particular unique patient, unique doctor and unique situation. The only guideline the authors can provide in this regard is to remind us all to consider relevance with all patients in all situations, and from the patient’s perspective. Even more important than the service to ophthalmologists is the benefit to patients that will result from thoughtful use of these guidelines.We need, also, to remember that diagnoses are generic, and that within every diagnosis there are differences. For example what does a diagnosis of primary open angle mean? Some of those affected will rapidly go blind despite the most thoughtful treatment and others will keep their sight even without treatment. What does a diagnosis of Chandler’s Syndrome mean? In some, surgery works well, and, in others, poorly. So one never directs diagnosis and treatment at a condition, but rather at the person, the objective being the wellness of that person.The previous European Glaucoma Society Guidelines are used internationally. It is good that the EGS is again providing updated, useful information.The Guidelines are a practical, inspirational contribution.George L. Spaeth, BA, MD.Esposito Research Professor, Wills Eye Hospital/Sidney Kimmel Medical College/Thomas Jefferson Universitywww.eugs.orgThe Guidelines writers, authors and contributorsAugusto Azuara-Blanco (Editor)Luca BagnascoAlessandro BagnisJoao Barbosa BredaChiara BonzanoAndrei BrezhnevAlain BronCarlo A. CutoloBarbara CvenkelStefano GandolfiTed Garway HeathIlmira GazizovaGus GazzardFranz GrehnAnders HeijlCornelia HirnGábor HollóAnton HommerMichele IesterIngrida JanulevicieneGauti JóhannessonMiriam KolkoTianjing LiJosé Martínez de la CasaFrances Meier-GibbonsMaria MusolinoMarta PazosNorbert PfeifferSergey PetrovLuis Abegao PintoRiccardo ScottoIngeborg StalmansGordana SunaricMégevandErnst TammJohn ThygesenFotis TopouzisMarc Töteberg-HarmsCarlo E. Traverso (Editor)Anja TuulonenZoya VeselovskayaAnanth ViswanathanIlgaz YalvacThierry ZeyenGuidelines CommitteeAugusto Azuara-Blanco (Chair)Carlo E. Traverso (Co-chair)Manuele Michelessi (NGP Co-chair)Luis Abegao PintoMichele IesterJoao BredaCarlo A. CutoloPanayiota FountiGerhard GarhoeferAndreas KatsanosMiriam KolkoFrancesco OddoneMarta PazosVerena Prokosch-WillingCedric SchweitzerAndrew TathamMarc Toteberg-HarmsAcknowledgementsAnja TuulonenTed Garway HeathRichard WormaldTianjing LiManuele MichelessiJenny BurrAzuara-Blanco for their methodological oversight.Tianjing Li and Riaz Qureshi (US Cochrane Eye and Vision Group) and Manuele Michelessi (EGS) for leading the evidence review.Manuele MichelessiGianni VirgiliJoao Barbosa BredaCarlo A. CutoloMarta PazosAndreas KatsanosGerhard GarhoferMiriam KolkoVerena ProkoschPanayota FountiFrancesco OddoneAli Ahmed Al RajhiTianjing LiRiaz Qureshi and Azuara-Blanco for their contribution to the evidence review.Karen Osborn and Joanna Bradley from Glaucoma UK charity for their contribution to the section: ‘What matters to patients’ (https://glaucoma.uk)Additional contributions were made by the following people on specific topicsEleftherios AnastasopoulosPanayiota FountiGus GazzardFranz GrehnAnders HeijlGábor HollóFotis TopouzisAnja TuulonenAnanth ViswanathamThe team of Clinica Oculistica of the University of Genoa for medical editing and illustrationsLuca BagnascoAlessandro BagnisChiara BonzanoCarlo A. CutoloMichele LesterMaria MusolinoRoberta ParodiRiccardo ScottoWe would like to thank the following colleagues for their help in reviewing/editing section I.7. Landmark randomised controlled trials for glaucomaJoe CaprioliTed Garway Heath Gus Gazzard Divakar Gupta Anders Heijl Michael Kass Stefano Miglior David Musch Norbert Pfeiffer Thierry ZeyenExternal reviewsWe would like to thank the following societies and experts:World Glaucoma Association:Parul IchhpujaniMonisha NongpiurTanuj DadaSola OlawoyeJayme ViannaMin Hee SuhFarouk GarbaSimon SkalickyAlex HuangFarouk GarbaPradeep RamuluVerena ProkoschCarolina Gracitelli;American Glaucoma Society:Josh Stein;and Latin-American Glaucoma Society:Daniel GrigeraWe would like to thank the external reviewers whose comments are listed on https://www.eugs.org/eng/guidelines.aspThe EGS executive committeeTed Garway Heath (President)Fotis Topouzis (Vice President)Ingeborg Stalmans (Treasurer)Anja Tuulonen (Past President)Luis Abegao PintoAndrei BrezhnevAlain BronGauti JóhannessonNorbert PfeifferThe board of the European Glaucoma Society FoundationCarlo E. Traverso (Chair)Fotis Topouzis (Vice Chair)Franz GrehnAnders HeijlJohn ThygesenThierry ZeyenGlossary5-FU 5-fluorouracilAAC Acute angle closureACG Angle closure glaucomaAGIS Advanced glaucoma intervention studyAH Aqueous humourAI Artificial intelligenceALT Argon laser trabeculoplastyBAC Benzalkalonium chlorideCCT Central corneal thicknessCDR Cup to disc ratioCIGTS Initial glaucoma treatment studyCNTGS Collaborative normal tension glaucoma studyDCT Dynamic contour tonometryEAGLE Effectiveness of early lens extraction for the treatment of primary angle closure glaucomaEGPS European glaucoma prevention studyEGS European glaucoma societyEMA The european medicines agencyEMGT Early manifest glaucoma trialFC Flow chartFDT Frequency doubling technologyFC Fixed combinationFL Fixation lossesFN False negativesFP False positiveGAT Goldmann applanation tonometryGHT The glaucoma hemifield testGRADE Grading of recommendations, assessment, development and evaluationsHRT Heidelberg retina tomographyICE Irido-corneal endothelial syndromeIOL Intraocular lensIOP Intraocular pressureITC Iridotrabecular contactIV IntravenousLIGHT Laser in glaucoma and ocular hypertension trialLPI Laser peripheral iridotomyLV Loss varianceMD Mean defect or mean deviationMMC Mitomycin CNCT Non-contact tonometryNd:YAG Neodymium-doped yttrium aluminum garnetNTG Normal tension glaucomaOAG Open angle glaucomaOCT Optical coherence tomographyOHT Ocular hypertensionOHTS The ocular hypertension treatment studyONH Optic nerve headORA Ocular response analyserOSD Ocular surface diseasePAC Primary angle closurePACG Primary angle closure glaucomaPACS Primary angle closure suspectPAS Peripheral anterior synechiaePCG Primary congenital glaucomaPDS Pigment dispersion syndromePGA Prostaglandin analoguePOAG Primary open angle glaucomaPG Pigmentary glaucomaPSD Pattern standard deviationPXF Pseudoexfoliation syndromePXFG Pseudoexfoliation glaucomaRCT Randomised controlled trialRNFL Retinal nerve fiber layerRoP Rate of progressionSAP Standard automated perimetrySITA Swedish interactive threshold algorithmSLT Selective laser trabeculoplastySWAP Short-wavelength automated perimetryTLPI Thermal laser peripheral iridoplastyTM Trabecular meshworkUBM Ultrasound biomicroscopyUGH Uveitis-glaucoma-hyphema syndromeUKGTS United Kingdom glaucoma treatment studyVEGF Vascular endothelial grow